The Effect of Digital Literacy and Sharia Financial Literacy on Consumptive Behavior in Purchasing Muslim Fashion with the Use of Sharia Digital Payment - Hoirullah Hoirullah; Elfira Maya Adiba (Academia Open, 2026)
General Background Consumption within Islamic economics emphasizes moderation and adherence to sharia principles, particularly amid rapid digitalization of financial transactions. Specific Background The expansion of sharia-based digital payment systems alongside the growth of Muslim fashion consumption in Madura highlights the relevance of digital literacy and sharia financial literacy in shaping consumer behavior. Knowledge Gap Prior studies largely focus on conventional digital payments and general regions, with limited empirical evidence addressing sharia digital payments, consumptive behavior, and local Islamic socio-cultural contexts in Madura. Aims This study examines the relationships between digital literacy, sharia financial literacy, consumptive behavior in Muslim fashion purchases, and the mediating role of sharia digital payment usage among the Madurese community. Results Using a quantitative approach with PLS-SEM on data from 384 respondents, the findings show that digital literacy and sharia financial literacy are significantly associated with sharia digital payment usage and consumptive behavior, while sharia digital payments also exhibit a direct relationship with consumptive behavior and mediate both literacy variables. Novelty The study integrates digital literacy and sharia financial literacy within a single empirical framework by positioning sharia digital payment usage as a mediating construct in Muslim fashion consumption. Implications These findings provide evidence-based insights for policymakers, Islamic financial institutions, and educators to design literacy programs and sharia-compliant digital payment services aligned with local values and consumption patterns in Muslim-majority regions. Highlights: Literacy-related competencies are statistically associated with transactional patterns in sharia-based payment systems. Payment platform utilization functions as a mediating mechanism linking literacy dimensions to purchasing tendencies. Empirical evidence from Madura confirms the relevance of local Islamic contexts in digital consumption studies. Keywords: Digital Literacy, Islamic Financial Literacy, Consumptive Behavior, Islamic Digital Payment.